LABORATORY PREDICTORS OF RAPID HIV DEVELOPMENT IN CHILDREN - V. B. Denisenko; E. N. Simovanyan (LLC "Diagnostics and Vaccines", 2015)
91 children vertically infected with HIV were examined. 26% of the patients, developed HIV infection rapidly with its subsequent development into AIDS in the first two years of life. Multifactorial logistic regression model demonstrated that independent predictors of rapid HIV-infection progression in children were HIV blood viral load 300 000 cop./ml and CD4+-lymphocytes count 20% in the age of six months. The use of HIV blood viral load level as a prognostic test is preferred because of higher sensitivity (91,3%) and specificity (97,1%).